CCR2 mediates the adverse effects of LPS in the pregnant mouse. Issue 2 (10th October 2019) - Hua, Renyi; Edey, Lydia F; O'Dea, Kieran P; Howe, Laura; Herbert, Bronwen R; Cheng, Weiwei; Zheng, Xia; MacIntyre, David A; Bennett, Philip R; Takata, Masao; Johnson, Mark R
Abstract: In our earlier work, we found that intrauterine (i.u.) and intraperitoneal (i.p.) injection of LPS (10-μg serotype 0111:B4) induced preterm labor (PTL) with high pup mortality, marked systemic inflammatory response and hypotension. Here, we used both i.u. and i.p. LPS models in pregnant wild-type (wt) and CCR2 knockout (CCR2−/−) mice on E16 to investigate the role played by the CCL2/CCR2 system in the response to LPS. Basally, lower numbers of monocytes and macrophages and higher numbers of neutrophils were found in the myometrium, placenta, and blood of CCR2−/− vs. wt mice. After i.u. LPS, parturition occurred at 14 h in both groups of mice. At 7 h post-injection, 70% of wt pups were dead vs. 10% of CCR2−/− pups, but at delivery 100% of wt and 90% of CCR2−/− pups were dead. Myometrial and placental monocytes and macrophages were generally lower in CCR2−/− mice, but this was less consistent in the circulation, lung, and liver. At 7 h post-LPS, myometrial ERK activation was greater and JNK and p65 lower and the mRNA levels of chemokines were higher and of inflammatory cytokines lower in CCR2−/− vs. wt mice. Pup brain and placental inflammation were similar. Using the IP LPS model, we found that all measures of arterial pressure increased in CCR2−/− but declined in wt mice. These data suggest that the CCL2/CCR2 system plays a critical role in the cardiovascular response to LPS and contributes to pup death but does not influence the onset of inflammation-induced PTL. Abstract : This study used mouse models of preterm labour and sepsis to show that during pregnancy the CCL2/CCR2 system is important in the cardiovascular response to sepsis but while it delays pup death it does not delay LPS-induced preterm labour.